2017
DOI: 10.1155/2017/1675982
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Seismic Behavior of a Single-Tower Cable-Stayed Bridge Subjected to Near-Field Earthquakes

Abstract: Cable-stayed bridges are quite sensitive to large amplitude oscillations from earthquakes and seismic damage was observed for Shipshaw Bridge and Chi-Lu Bridge during past earthquakes. In order to investigate seismic damage of cable-stayed bridges, a 1 : 20 scale model of a single-tower cable-stayed bridge with A-shaped tower was designed, constructed, and tested on shake tables at Tongji University, China. One typical near-field ground motion was used to excite the model from low to high intensity. Test resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Tang et al [19] carried out a shake-table experiment to investigate the behavior of a reinforced-concrete low-cap-pile group embedded in this type of ground. There are many studies on the response of the platform under strong earthquakes [20,21]. The dynamic Shock and Vibration 5 …”
Section: Related Research On High Pile Cap and Low-pile Capmentioning
confidence: 99%
“…Tang et al [19] carried out a shake-table experiment to investigate the behavior of a reinforced-concrete low-cap-pile group embedded in this type of ground. There are many studies on the response of the platform under strong earthquakes [20,21]. The dynamic Shock and Vibration 5 …”
Section: Related Research On High Pile Cap and Low-pile Capmentioning
confidence: 99%
“…As highlighted by the damage of Chi-Lu Bridge (Chadwell and Fenves 2003) and the shake test results of the cable-stayed bridge model (Yi and Li 2017), several composing parts of cable-stayed bridges, namely the tower, deck and cables might suffer damage during earthquakes. However, since cable-stayed bridges represents the key points transport networks, only the tower was permitted with controllable damage under extreme seismic events for Rion-Antirion Bridge (Combault and Teyssandier 2005) and also in Japanese Code (Japan Road Association 2002).…”
Section: Damage States Of the Structurementioning
confidence: 99%
“…Past research has studied in detail the dynamic behaviour of cables, by determining initially a way to estimate the damping in stay cables using complex-mode analysis [3,4]. Even though actions such as wind, fatigue, or temperature may have a higher role on the behaviour of cables, it has been shown that earthquakes may too induce large variations in the internal forces of cables [5], which led previous research to look at various cable layouts in cable-stayed bridges by employing seismic-risk analyses [6]. A comprehensive review on the behaviour of cables subjected to earthquakes [7] also emphasizes the benefits of studying the cable-structure interaction in the seismic response of cable-stayed bridges.…”
Section: Introductionmentioning
confidence: 99%